2014
DOI: 10.1016/j.jconrel.2013.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal ablation of tumor cells using a single-walled carbon nanotube–peptide composite

Abstract: Single-walled carbon nanotubes (SWCNTs) are known to have great potential for biomedical applications such as photothermal ablation of tumor cells in combination with near-infrared (NIR) irradiation. In this study, the photothermal activity of a novel SWCNTs composite with a designed peptide having a repeated structure of H-(-Lys-Phe-Lys-Ala-)7-OH [(KFKA)7] against tumor cells was evaluated in vitro and in vivo. The SWCNT-(KFKA)7 composite demonstrated high aqueous dispersibility that enabled SWCNTs to be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 30 publications
1
74
0
1
Order By: Relevance
“…This suggests the great potential of an SWCNTpeptide composite for use in photothermal cancer therapy. 46 We obtained similar results using L02 and HepG2 cells treated with SWNHs at lower dosages (1.5-6.0 µg/mL, 4 mL of culture matrix).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This suggests the great potential of an SWCNTpeptide composite for use in photothermal cancer therapy. 46 We obtained similar results using L02 and HepG2 cells treated with SWNHs at lower dosages (1.5-6.0 µg/mL, 4 mL of culture matrix).…”
Section: Discussionsupporting
confidence: 72%
“…Single-walled carbon nanotubes (SWCNTs) are known to have great potential for biomedical applications such as photothermal ablation of tumor cells in combination with near-infrared irradiation. Hashida et al 46 found that the photothermal activity of a novel SWCNT composite with a designed peptide having a repeated structure of H -( -Lys-Phe-Lys-Ala-)7-OH ([KFKA]7) against tumor cells. The SWCNTs-(KFKA)7 composite demonstrated high aqueous dispersibility that enabled SWCNTs to be used in tumor ablation.…”
Section: Discussionmentioning
confidence: 99%
“…39 In this study, we used these NPs to evaluate their ability for tumor size reduction by PTT technique. At first, for improving the dispersibility of MWNTs in water, the hydrophilic polymer PEG was used to wrap the surface of the nanotubes.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperthermia also increases the vascular permeability of tumor compared with normal vasculature, which can facilitate the delivery of anticancer drugs into tumors. 39 Therefore, localization of plasmonic NPs in the tumor region can be an efficient strategy for treatment of solid tumors. In this in vivo ablation experiment, O-CNT-PEG was injected into the melanoma tumor, and then the solid tumor region was irradiated.…”
mentioning
confidence: 99%
“…En consecuencia los efectos térmicos generados por NTC pueden tener ventajas terapéuticas importantes, ya que estudios fármaco-cinéticos han observado que los NTC internalizados en ratones por diferentes procedimientos no generan efectos tóxicos ( Hashida, 2014). El uso de la radiación IR (700 -1100-nm) para la inducción de la hipertermia es particularmente atractiva porque los tejidos vivos no absorben fuertemente en este rango y la luz NIR externa puede penetrar el tejido normal sin problemas y permitir la ablación de las células en las cuales se hallan los NTC.…”
Section: Introductionunclassified